Elucidating VSMC phenotypic transition mechanisms to bridge insights into cardiovascular disease implications - Xin, Yuning; Zhang, Zipei; Lv, Shan; Xu, Shan; Liu, Aidong; Li, Hongyu; Li, Pengfei; Han, Huize; Liu, Yinghui (Frontiers in Cardiovascular Medicine, 2024)
Cardiovascular diseases (CVD) are the leading cause of death worldwide, despite advances in understanding cardiovascular health. Significant barriers still exist in effectively preventing and managing these diseases. Vascular smooth muscle cells (VSMCs) are crucial for maintaining vascular integrity and can switch between contractile and synthetic functions in response to stimuli such as hypoxia and inflammation. These transformations play a pivotal role in the progression of cardiovascular diseases, facilitating vascular modifications and disease advancement. This article synthesizes the current understanding of the mechanisms and signaling pathways regulating VSMC phenotypic transitions, highlighting their potential as therapeutic targets in cardiovascular disease interventions.